Internet Addiction and Stressors Causing Internet Addiction in Primary School Children during the COVID-19 Pandemic: A Descriptive and Cross-Sectional Study from Turkey - Aközlü, Zeynep; Kolukısa, Tuğçe; Öztürk Şahin, Özlem; Topan, Aysel (Addicta: The Turkish Journal on Addictions, 2021)
In this study, we aimed to examine the status of internet addiction in children and the stress factors causing it during the coronavirus disease 2019 (COVID-19) pandemic. This study was a descriptive and cross-sectional study. The study sample included 154 parents of 7- to 10-year-old students. Participant information form and the Family-Child Internet Addiction Scale were used as data collection tools. The data of the study were collected with a questionnaire (via Google Forms) between July 15 and December 15, 2020. Of the children participating in the study, 90.3% (n=139) showed no symptoms and 9.7% (n=15) showed limited symptoms in terms of internet addiction. The total mean score that the children obtained from the scale was found to be 24.6±16.9. It was observed that the frequency of a child playing games with parents, the parents watching news about COVID-19 with the child, and the child being frequently warned about the COVID-19 precautions increased the children’s internet addiction scores (p